Ultrasound-guided serratus anterior plane block for analgesia after thoracic surgery - Semyonov, Michael (J Pain Res, 2019)
BACKGROUND: Patients who undergo surgical procedures that impair the integrity of the chest wall frequently experience extremely severe postoperative pain. Opiates and weaker analgesics, such as nonsteroidal anti-inflammatory drugs (NSAIDs), are not sufficiently effective in achieving control of severe pain and might cause respiratory and gastrointestinal complications. In the past decade, there has been an increased interest in the use of regional nerve blocks for post-thoracoscopy and post-thoracotomy analgesia. METHODS: This is a prospective, randomized, double-blind and single-center study. We recruited 104 patients who underwent elective thoracoscopy. Prior to surgery, the participating patients were randomized into one of two study groups: Group 1- the “standard control group” that received standard postoperative pain control with intravenous opioids, NSAIDs and acetaminophen (paracetamol) and Group 2- the “block group” that was treated by ultrasound-guided serratus anterior plane (SAP) block (a single injection of 0.25% bupivacaine hydrochloride 2 mg/kg plus dexamethasone 8 mg) with standard postoperative pain control regimen. We compared the clinical, laboratory, and postoperative pain assessment data of both groups. RESULTS: Patients in the SAP block Group 2 reported significantly lower levels of pain after thoracic surgery as assessed by their visual analog scale scores, as compared to the patients in the standard pain control Group 1 (P<0.001). The total dosage of morphine and tramadol required for pain relief during the first hours after surgery was significantly lower in the patients who received SAP block. Also, the incidence of vomiting after surgery was significantly lower among the patients who received SAP block than among the patients who received standard pain control. CONCLUSION: The results of the present study suggest that SAP block is an effective adjuvant treatment option for post-thoracic surgery analgesia. Compared to the current methods used for post-thoracic surgery pain relief, SAP block has some significant merits, particularly its ease of use and its low potential for side effects.